Bilateral Stroke in Geriatric – Role of Health Care Professionals – An Evidenced Analysis for to Be Redefined - Dr.S.S.Subramanian (International Journal of Pharma and Bio Sciences, 2022)
An increasing longevity globally were recorded associated health complications, among geriatric population like falls, stroke, and were under researched. Health care records of subjects above 80 years and bilateral stroke with their prevalence, causes functional recovery were less reported. Hence this clinical presentation with evidenced strives to analyse unaddressed bilateral stroke with its prevalence, risk factors, causes along with functional pattern of recovery gets more significant. As an increasing longevity octogenarian subjects likely to develop bilateral stroke are more in coming years. Bilateral stroke were found to diminish quality of life and increase the level of dependency especially among geriatric subjects. Equally they were linked with longer hospitalization and higher mortality. Aims and objectives of this research were to analyse causes, prognosis and functional recovery among bilateral stroke. This research analysis for 3 years on an octogenarian subject who was obese, hypertensive, diabetic, hyperlipidemia. This longitudinal research were from June 2018 - May 2021. With family support, proper medical intervention, regular physiotherapy functional independence and cognition can be promoted even at the age of 90 years were key outcome, Findings of this research can be used to identify causes, treat them towards prevention and how to functionally accelerate recovery of bilateral stroke subjects in years to come. Also every effort should be driven positively irrespective of age, major thrust of this research.